Feasibility of Implementation Mapping for Integrative Medical Group Visits - Roth, Isabel J. (J Altern Complement Med, 2021)
Objectives: Implementation science is key to translating complementary and integrative health intervention research into practice as it can increase accessibility and affordability while maximizing patient health outcomes. The authors describe using implementation mapping to (1) identify barriers and facilitators impacting the implementation of an Integrative Medical Group Visit (IMGV) intervention in an outpatient setting with a high burden of patients with chronic pain and (2) select and develop implementation strategies utilizing theory and stakeholder input to address those barriers and facilitators. Design: The authors selected a packaged, evidence-based, integrative pain management intervention, the IMGV, to implement in an outpatient clinic with a high burden of patients with chronic pain. The authors used implementation mapping to identify implementation strategies for IMGV, considering theory and stakeholder input. Stakeholder interviews with clinic staff, faculty, and administrators (n = 15) were guided by the Consolidated Framework for Implementation Research. Results: Based on interview data, the authors identified administrators, physicians, nursing staff, and scheduling staff as key stakeholders involved in implementation. Barriers and facilitators focused on knowledge, buy-in, and operational procedures needed to successfully implement IMGV. The implementation team identified three cognitive influences on behavior that would impact performance: knowledge, outcome expectations, and self-efficacy; and three theoretical change methods: cue to participate, communication, and mobilization. Implementation strategies identified included identifying and preparing champions, participation in ongoing training, developing and distributing educational materials, and organizing clinician implementation team meetings. Conclusions: This study provides an example of the application of implementation mapping to identify theory-driven implementation strategies for IMGV. Implementation mapping is a feasible method that may be useful in providing a guiding structure for implementation teams as they employ implementation frameworks and select implementation strategies for integrative health interventions.